Soil salinity, micronutrients and passion fruit production irrigated with saline water and using organomineral fertilization - Souza, José Thyago Aires; Cavalcante, Lourival Ferreira; Nunes, Jarisson Cavalcante; Araújo, Danila Lima; Oliveira, Flaviano Fernades (Scientia Plena, 2020)
The experiment was conducted in the city of Remigio, Paraiba State, Brazil, from July/2013 to May/2014. The aim of this work is to evaluate the effects of the saline water, bovine biofertilizer and potassium source on soil salinity, micronutrients and sodium contents in the leaf dry matter, and on the production of yellow passion fruit plants cv BRS Gigante Amarelo. The treatments were distributed in randomized blocks subdivided into plots using the factorial scheme 2 × (2 × 2). It refers to the main plot as two different irrigation waters with electrical conductivities of 0.35 and 4.00 dS m-1, and the subplots as the combination between the biofertilizer application and exemption with different potassium sources: the conventional potassium chloride (KCl) and the polymer-coated one. The increase in the electrical conductivity of the irrigation water increased the initial soil salinity from 0.36 to 3.43 and after to 5.43 dS m-1. It also increased the leaf contents of Fe2+ and Na+. The biofertilizer increased the Zn2+ content in the leaf dry matter of the passion fruit plants, while the fertilization with polymer-coated KCl increased the B content and reduced the Mn2+ one as compared to the conventional KCl. The plants, at the beginning of the flowering phase, although their deficiencies of all micronutrients, presented satisfactory productivity levels whether the national average numbers are considered.